Study of knowledge and attitude towards breastfeeding in antenatal mothers at Chamarajanagara Institute of Medical Sciences, Chamarajanagar, India - Ramachandra, Pradeep Musale; Hiremath, Nayana Davanagere (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: exclusive breast feeding practice is major pillar in preventing infant mortality. This study was undertaken to know the knowledge and attitude of antenatal mothers towards breast feeding. Methods: this is a cross sectional study in our hospital in which 264 antenatal mothers were included after verbal consent. Antenatal mothers were explained about the study, their knowledge and attitude regarding breast feeding is assessed by questionnaire. Study will be analysed by appropriate statistical analysis. Results: In total of 264 antenatal mothers, most of them were between 20-25 years, majority in third trimester. Among them 68.2% knows breast feeding should be initiated within first hour of delivery, 90.2% is for no prelacteal feeds and 95.8% wants to feed colostrum. Only 42.4% wants to continue breastfeeding for two years. About 62.9% of antenatal mothers wants to supplement the child with food after six months.81.8% knows breast feeding is not only helpful to the baby but also it prevents breast cancer in mother later in life. 21.2% wants to feed complimentary feeds as early as 3 months. Conclusions: our study on knowledge of breast feeding among antenatal mothers shown most of them are against prelacteal feeds and wants to feed colostrums, but initiation of breast feeding within first hour of birth and weaning after six months and continuation of breast milk up to two years is lagging. Multiple educational sessions, visual aids, pamphlets, electronic media, counseling during antenatal period and in early post natal period is necessary to inculcate appropriate knowledge on breast feeding.